Salfingoophorectomy pada Giant Ovarian Mature Cystic Teratoma disertai Hernia Umbilikal - Rachmatia Ramadanti; Yusmaidi (CV. Jasa Sukses Abadi, 2020)
Giant ovarian cysts are tumor which have a diameter > 10 cm in radiology or reaching above the umbilicus. Symptoms of tumor are usually asymptomatic, but can cause nonspecific stomach disorders including pain, nausea, and vomiting. In teratomas can be found sebaceous glands, sweat glands, hair follicles, fatty tissue. Investigations can be performed ultrasonography and CT-Sacn. The treatment is performed surgically by laparotomy or laparoscopy. In this case Nn.S, 22 years old came with complaints of an enlarged abdomen since 2 years ago. The physical examination of the patient are compost mentis. Blood pressure 130/100 mmHg, heart rate 105x / minute, respiratory rate 24x / minute, temperature 37.0oC. Examination of the abdomen showed an enlargement of the abdomen equivalent to 9 months gestational age with a 103 cm abdominal circumference, bowel sounds (+) 10x / minute, on percussion tympanic to deaf, found palpation hard palpated, negative tenderness. At CT scan shows that teratomas are quite large in the abdominal cavity which deviates the intrabomen into peripheral organs.